The Relationship Between Body Image And Psychological Well Being In Senior High School Students: Hubungan Antara Body Image Dengan Psychological Well Being Pada Siswi Sekolah Menengah Atas - Amaliyah Syabana; Eko Hardi Ansyah (Universitas Muhammadiyah Sidoarjo, 2022)
This research is motivated by the phenomenon of psychological well being experienced by students. The purpose of this study was to determine the relationship between body image and psychological well being in students of SMA Muhammadiyah 4 Porong. This research is a quantitative research with correlational quantitative method. The population in this study were all students of SMA Muhamadiyah 4 Porong, totaling 62 students. The sample in this study amounted to 62 students with saturated sampling technique. In the data collection technique, the researcher uses a psychological scale, this type of data collection uses a Likert scale in the form of a body image scale (ɑ = 0.797) and a psychological well being scale (ɑ = 0.948). The data analysis technique used Pearson's product-moment correlation with the help of SPSS 22.0. The results of the data analysis of this study indicate that the correlation coefficient (rxy) is 0.246 with a significance of 0.027 <0.05, which means that there is a significant positive relationship between body image and psychological well being in students of SMA Muhamadiyah 4 Porong. The effect of body image on psychological well being in this study was 6.1%.